if (a^2 - b^2 )sinA + 2ab. cosA = a^2 + b^2 ,find the value of tanA
Answers
Answer
Solution
Given
(a² - b²)sinA + 2ab·cosA = a² + b²
We can write it as
2ab·cosA = a² + b² - (a² - b²)sinA
Squaring both sides, we get
(2ab·cosA)² = (a² + b²)² + (a² - b²)²sin²A - 2(a² + b²)(a² - b²)sinA
Using, sin²A = 1 - cos²A,
→ 4a²b²·cos²A = a⁴ + b⁴ + 2a²b² + (a² - b²)²(1 - cos²A) - 2(a² + b²)(a² - b²)sinA
→ 4a²b²·cos²A = (a² + b²)² + (a² - b²)²- (a² - b²)²cos²A - 2(a² + b²)(a² - b²)sinA
Transporting 4a²b²·cos²A on other side
→ (a² + b²)² + (a² - b²)² - a⁴cos²A - b⁴cos²A + 2a²b²·cos²A - 4a²b²·cos² - 2(a⁴ - b⁴)sinA = 0
It becomes after simplifying
→ (a² + b²)² + (a² - b²)² - (a⁴cos²A + b⁴cos²A + 2a²b²·cos²A) - 2(a⁴ - b⁴)sinA = 0
Taking out negative cos²A common
→ (a² + b²)² + (a² - b²)² - (cos²A)(a² + b²)² - 2(a⁴ - b⁴)sinA = 0
Taking out (a² + b²)² common
→ (a² + b²)²(1 - cos²A) + (a² - b²)² - 2(a² + b²)(a² - b²)sinA = 0
Using (1 - cos²A) = sin²A
→ (a² + b²)²(sin²A) + (a² - b²)² - 2(a² + b²)(a² - b²)sinA = 0
Using a² + b² - 2ab = (a - b)²
→ [(a² + b²)sinA - (a² - b²)]² = 0
→ (a² + b²)sinA - a² + b² = 0
→ sinA = (a² - b²)/(a² + b²)
Now, we know that cos²A = 1 - sin²A
So, cos²A =
It becomes, cos²A =
Using a² - b² = (a + b)(a - b),
cos²A =
cos²A =
Taking under root on both sides,
cosA =
We know that tanA = sinA/cosA
So, tanA =
TanA =